Ekranisasi Novel El Karya Luluk H.F.KE Dalam Film El Karya Sutradara Findo Purwono - Leony Silitonga; Karin Hanna Geofani Br. Manullang; Ika Febriana (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
In recent years, the world of cinema cannot be separated from literary works. Many literary works, one of which is a novel, are used as inspiration to produce a film. Novels that have popularity and high sales levels are able to attract producers to adapt novels into film form. The focus of this research is to describe the ecranization of the novel into the EL film, which includes (1) ecranization of the plot, (2) ecranization of the characters, and (3) ecranization of the setting. The approach used in this study is a qualitative approach with descriptive methods. The main instrument in this research is the researcher himself. The source of the research data is the novel el by luluk h.f.ke in the film el by director findo purwono. Data collection techniques are reading, watching, and recording data contained in EL novels and films. The results of this study's data analysis indicate that there is a process of ecranizing the novel into EL film which includes adding, shrinking, and varying changes.